Sexual dimorphism in LC-MS/MS-based vitamin D metabolite profiling and nutrition-acquired biochemical osteomalacia among adolescents - Sabico, Shaun; Al-Daghri, Nasser M.; Alenad, Amal; Al-Saleh, Yousef; Khattak, Malak N. K.; Wani, Kaiser; Alnaami, Abdullah M.; Reginster, Jean-Yves; Alokail, Majed S.; Cavalier, Etienne (Frontiers in Nutrition, 2025)
IntroductionWe previously reported a high prevalence of biochemical osteomalacia among apparently healthy Arab adolescents using combined mineralization markers. This study examined whether advanced LC-MS/MS–based vitamin D metabolite profiling, including the vitamin D metabolite ratio (VMR), can serve as indicators of biochemical osteomalacia in Arab adolescents.MethodsA total of 976 age- and body mass index-matched adolescents (522 girls, mean age 14.9 ± 1.8 years, body mass index, BMI 23.0 ± 5.9; 454 boys, mean age 14.9 ± 1.7 years, BMI 23.7 ± 5.8) were included in this cross-sectional study. Anthropometrics and biochemical parameters [glucose, lipid profile, calcium (Ca), inorganic phosphorus (Pi), alkaline phosphatase (ALP)] were measured using routine assays. Circulating vitamin D metabolites [24,25(OH)₂D (24, 25 VD), VD2, VD3, total VD] were quantified using LC-MS/MS, and VMR calculated as [24,25 VD/VD] × 100. Deficiency cut-offs were: VD <30 nmol/L, 24,25 VD <3.0 nmol/L, VMR <4%. Biochemical osteomalacia was defined as ≥ 2 abnormal markers (low VD, high ALP, low Ca, or low Pi).ResultsAll vitamin D metabolites were significantly lower in the biochemical osteomalacia group. Overall, VD showed the highest predictive value (AUC 0.71, Youden index 0.40). Stratified analyses revealed VMR as a modest marker in girls (AUC 0.60), while VD3 performed best in boys (AUC 0.77, Youden index 0.60).ConclusionVD metabolites as a single test are modest predictors of biochemical osteomalacia in adolescents and differ in accuracy according to sex. Findings in this study should be interpreted as exploratory rather than diagnostic, serving to generate hypotheses and lay groundwork for future clinical and public health applications.